Research on the Impact of Green Technology Innovation on Energy Total Factor Productivity, Based on Provincial Data of China - Wang, Mengxin; Li, Yanling; Liao, Gaoke (Frontiers in Environmental Science, 2021)
Against the background of carbon peaking and carbon neutralization, green technology innovation plays an important role in promoting the energy total factor productivity (TFP). Based on China's provincial data, this paper verifies the impact of green technology innovation on energy TFP by constructing a panel threshold model, and analyzes its influence mechanism on the basis of the mediating effect test. Based on regional division, the heterogeneity of the impact of green technology innovation on energy TFP is studied. It is found that: first, with the level of economic development as the threshold variable, there is a threshold effect in the impact of green technology innovation on energy efficiency; second, green technology innovation has an impact on energy efficiency through industrial structure upgrading, that is, industrial structure has a mediating effect in the influence mechanism; third, there is heterogeneity in the impact of green technology innovation on energy efficiency among different regions in China, and the threshold effect only exists in the western region, since the central and eastern regions have crossed a certain development stage.